Vascular plants of oxbow lakes of Turvo River, Upper Paraná River basin, São Paulo State, Brazil - de Araujo, Renato Braz [UNESP]; Langeani, Francisco [UNESP]; Ranga, Neusa Taroda [UNESP] (My University, 2010)
Vascular plants were investigated in oxbow lakes of Turvo River, Upper Paraná River basin, between Icém and Nova Granada municipalities, state of São Paulo, Brazil. In this region, six lagoons were sampled: Ganzella, Mustafá, Braço Morto, 45, Federal, and Parente. The survey showed a total of 54 species, 36 genera and 22 families. The species richest families were Poaceae, Cyperaceae, and Polygonaceae. Eichhornia crassipes (Pontederiaceae) was the single species encountered in all the six lakes. © 2010 Check List and Authors.
Keywords: Bracon; Cyperaceae; Eichhornia; Eichhornia crassipes; Magnoliophyta; Poaceae; Polygonaceae; Pontederiaceae; Tracheophyta